Acute intermittent porphyria: a test of clinical acumen. Issue 2 (3rd April 2017) - Dhital, Rashmi; Basnet, Sijan; Poudel, Dilli Ram; Bhusal, Khema Raj
ABSTRACT: Acute intermittent porphyria (AIP) is a rare autosomal dominant hepatic porphyria due to deficiency of hydroxymethylbilane synthase (HMBS), also known as porphobilinogen deaminase leading to accumulation of porphyrin precursors. However, gene defect alone is usually not sufficient to cause an acute attack, and many extrinsic factors play a role. Diagnostic tests are defined, but clinical suspicion is often delayed as symptoms mimic other common conditions. We report a case of a 18-year-old male with severe, persistent, and generalized abdominal pain along with marked hyponatremia, with subsequent development of altered mentation needing intensive care. He improved after infusion of intravenous dextrose. AIP can mimic many common surgical and medical conditions such as appendicitis, cholecystitis, pancreatitis, etc., and may lead to extensive diagnostics or surgical intervention if missed. Diagnosis of AIP requires high clinical suspicion. It should be considered in a patient with recurrent abdominal symptoms, intractable hyponatremia, along with neurological manifestations. Early diagnosis and treatment can prevent recurrent episodes and can potentially be lifesaving. Abbreviations: AIP: Acute intermittent porphyria; ALA: Aminolevulinic acid; PBG: Porphobilinogen